RANCANG BANGUN SISTEM PENGELOLAAN PERMUKIMAN DI KAWASAN PINGGIRAN METROPOLITAN (STUDI KASUS: KORIDOR JALAN CIRENDEU, KABUPATEN TANGERANG) - Heripoerwanto, Eko D (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2008)
People who were seeking housing in relatively good environment in the fringe area of metropolitant have found themselves experiencing the negative impact of continuing suburban sprawl and housing growth, especially when basic infrastructures and urban services are insufficient. Together with the increasingenvironmental pressure caused by traffic jam and pollution, all of these condition have absolutely been lowering their amenities, then in turn their quality of life. The problems are whether is there any lack of specific steps in formulating the policy and if not, is there any gap beetween knowledge and action in implementingthe policy? This research tries to reveal what exactly the needed processes andntype of strategic planning are to produce to make a Sustainable SettlementnManagement System Modelling possible. The research intended to establish policy model through soft system methodology (SSM), which is considered the most suitable approach to this area, that is characterized by the interwoven ofunstructured problems involving multisectors, multiactors, and multidisciplines. The findings of the research are the need of a better processes in public policy formulation upon the fringe areas of metropolitan, by involving knowledgable persons. Using this mechanism, the research come to the conclusion that astrong policy on developing infrastructure and transportation as well as the provision of social-public facilities within walking distance in an integrated way with the development of housing and settlement in order to maintain the level of amenities are needed. In addition to these findings, community-based organization,such as home-owner asssociation, has to be established in order to allow a bigger room for community participation in implementing the public policy.